Formation of linguistic competence of a foreign language teacher (on the example of language) in the system of lifelong learning - Buhinska, Tetiana; Hladkoskok, Lesia; Khomenko, Oleksandr; Terletska, Liubov; Tanana, Svitlana (My University, 2021)
The purpose of the research is to establish the effectiveness of the introduction of an additional course inupgrade training courses, which is designed to inform English teachers about existing global educational programs for lifelong learning;determining the impact of introducing a set of educational activities aimed at the formation of linguistic competenceon the quality of knowledge. Based on the purpose outlined, it is planned to perform the research objectives as follows: •to explore the demographic and gender features ofstudents of advanced training courses for English teachers; •to reveal how the introduction of an additional course will improve the level of awareness of English teachers about opportunities of increasing their own linguistic competence throughout life through non-formal education, participation in international educational activities for professionaldevelopment, self-improvement. •to determine how much the professional level of teachers has increased after undergoing courses where the emphasis has been on a comprehensive development of the linguistic competence of the English teacher.
Keywords: linguistic competence, foreign language